Maharajah of Bikaner India - Purcell, Hugh (Haus histories, 2010)
The story of the Indian soldiery in the Great War needs a new telling and one important chapter of it will be about the Maharajah of Bikaner: Dashing, autocratic and a formidable public speaker, Ganga Singh commanded his own camel corps called the Ganga Risala, fought on the Western Front and in Egypt, became the first Indian general in the British Indian army and persuaded the maharajas to unite into the Chamber of Princes. As a result of this and his war record he was invited by Lloyd George to attend the Imperial War Conference in 1917 and then the Versailles Peace Conference two years later, where he persuaded the other delegates to include India in the new League of Nations, quite an achievement as it was not an independent nation. Less successfully he tried to prevent the dismemberment of Turkey.